Prevention of Frost Heave in the Surrounding Rocks of Tunnel for Ski Resorts. Issue 4 (October 2021) - Hou, Hongzhang; Fu, Dan; Luo, Sijia; He, Zhenglin
Abstract: Taking the four-season ski resort in Jilin Beishan as an example, this paper analyses the temperature field of surrounding rocks by applying the theory of transient thermal conductivity of semi-infinite large objects, and explains the necessity of insulation isolation layer and heating system setting. The structure and insulation performance of the insulation isolation layer are specified, and the flat wall steady-state thermal conductivity theory is used to calculate that the heat transfer on both sides of the insulation layer is about 29.66kW. This heat is not only a part of the cooling load of the snow resort refrigeration system, but also a part of the heat load of the wall heating system. For the refrigeration system, the COP value of the chiller is 2.5kW/kW. Even excluding the energy consumption of the transmission and distribution process, the annual power consumption of the cooling load alone is about 104, 000 KWH, which explains the importance of the temperature control system and insulation layer. The heat source of the heating system of this project innovatively adopts the waste heat of cooling generated in the refrigeration process. This measure makes the heating source of this project no longer consume fossil energy, resulting in significant energy saving and emission reduction benefits. As described, a tunnel ski resort similar to a new or rebuild one can be used as a reference. Some of the results can be applied to prevention of frost heave of traffic tunnels in high-cold and high-latitude areas.